Therapeutic drug monitoring in epilepsy: Can drug levels reliably measure drug adherence? - W. Olusanya, Adedunni; P. Arikawe, Adesina; S. Amao, Omowunmi; A. Busari, Abdulwasiu; A Danesi, Mustapha (The Nigerian Journal of Pharmacy, 2022)
Background: Drug adherence is often assessed from patients' reports and confifirmed with therapeutic drug monitoring. The study investigated the relationship between reports of drug adherence and drug levels of carbamazepine among adult patients on carbamazepine monotherapy. Methods: 84 consecutively consenting patients who had been on carbamazepine monotherapy for seizure control were recruited from the Neurology Clinic, LUTH, Idi-Araba, Lagos for the study. Adherence in the past month was assessed using a standard proforma. Drug levels were taken in the trough phase (just before the next dose of carbamazepine) and analyzed using high performance liquid chromatography. Results: Among the population studied, full adherence was reported in 45.2% of the participants while the remainder had missed one or more doses in the past month. Serum drug levels were found to be signifificantly higher in patient who reported full adherence compared to non-adherent patients (p<0.05). When levels were compared to the reference range of carbamazepine, 15.8% of the patient who reported good adherence had blood levels in the subtherapeutic range, while 21.7% who reported poor adherence had blood levels in the subtherapeutic range (p>0.05). Conclusion: Adherence is associated with higher drug levels, but both adherent and nonadherent patients had a similar likelihood of having serum drug blood levels in the subtherapeutic range. This calls for caution in the interpretation of drug levels as it relates to adherence. Further studies on standardization of therapeutic drug measurement to develop predictive tools for adherence are recommended.